Economic burden of comorbidities in psoriasis patients in the United States: results from a retrospective U.S. database - Steven R. Feldman; Haijun Tian; Isabelle Gilloteau; Patrick Mollon; Meng Shu (BMC Health Services Research, 2017)
Abstract Background Psoriasis is a multifactorial, inflammatory, skin disease associated with various comorbidities. The cost of those comorbidities is not well characterized. The present study assesses the incremental burden of comorbidities on healthcare resource utilization, direct costs and indirect costs associated with short-term disabilities among patients with psoriasis in the United States. Methods A retrospective, U.S. cohort analysis was conducted using a large claims database. Adult psoriasis patients with at least two diagnoses of psoriasis during the years 2010 and 2011 (one psoriasis diagnosis had to happen in the year 2010) and with continuous enrollment of medical and pharmacy benefits in the years 2010 and 2011 were included. Psoriasis patients were categorized and compared according to the presence or absence of pre-selected comorbidities in the year 2010. Adjusted annual direct (costs associated with outpatient, emergency room, and inpatient claims, and outpatient pharmacy claims) and indirect costs (short-term disabilities) was assessed in patients with and without comorbidities using a regression analysis, controlling for age, gender, and psoriasis severity in year 2010. Results In total, 56,406 patients (mean [SD]) age, 51.6 [14.6] years) were included in the analysis. The most prevalent comorbidities were hypertension (34.3%), hyperlipidemia (33.5%), cardiovascular disease (17.7%), diabetes (14.2%), and psoriatic arthritis (9.9%). Psoriasis patients with comorbidities used more healthcare resources than those without comorbidities. The incidence rate ratio (IRR) (95% CI) for patients with cardiovascular disease was 1.5 (1.4 − 1.5) for outpatient visits, 2.6 (2.4 − 2.8) for hospitalizations, and 2.3 (2.2 − 2.5) for ER visits, showing higher IRRs across all three types of resource use. The mean annual adjusted direct cost differences (i.e., incremental adjusted costs) in psoriasis patients with and without comorbidities were $9914.3, $8386.5, and $8275.1 for psoriatic arthritis, peripheral vascular disease, and cardiovascular disease, respectively. The mean annual incremental adjusted indirect costs of short-term disabilities were $1333, $1195, $994.9, and $996.6 for cerebrovascular disease, obesity, peripheral vascular disease, and depression, respectively. Conclusion The presence of comorbidities was associated with higher healthcare resource utilization and costs among patients with psoriasis.